Belle II pixel detector: performance of final DEPFET modules - Paschen, Botho; Ritzert, Michael (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2020)
A DEpleted P-channel Field Effect Transistor (DEPFET) based pixel detector was developed for the Belle II VerteX Detector (VXD). It is designed to achieve a good impact parameter resolution better than 15μm at the very high luminosity conditions of this experiment. In the first half of 2018 four final production modules have been deployed in the commissioning run of the detector and their performance is discussed.